The significance of supportive and undermining elements in the maternal representations of an unborn baby. (27th May 2018) - Rusanen, E.; Lahikainen, A. R.; Pölkki, P.; Saarenpää-Heikkilä, O.; Paavonen, E. J.
Abstract: Objective: The maternal representations of an unborn baby begin to develop during pregnancy. However, the factors that moderate them are not well identified. The objective of this study was to jointly explore supportive and undermining factors in the maternal representations of an unborn baby and motherhood. Methods: Cross-sectional data comprising 1646 women studied during the third trimester of pregnancy. Maternal expectations were measured using a 12-item self-report questionnaire, Mother's Representations about an Unborn Baby. Depression, anxiety, family atmosphere and adult attachment were measured using standardised questionnaires. Statistical analysis is based on multivariate linear regression analysis. Results: The most powerful predictors of a mother's prenatal expectations were the mother's educational status, age, closeness in adult relationships, higher levels of depressive symptoms and family atmosphere. In accordance with our hypothesis, depression was related to the mother's more negative expectations on their relationship with the unborn baby and on regularity in the baby's sleeping and eating patterns. A positive family atmosphere and the mother's ability for closeness and dependence (i.e. confidence) in adult relationships were related to more positive expectations of the mother–unborn baby relationship. On the other hand, stress, anxiety and adverse life events were not related to the mother's expectations of her unborn baby. Conclusions: The results may be helpful in identifying families who need early professional support and call for studies where the prenatal phase is explored as a proactive phase for the development of the child–parent relationship.